Using the formula for tan(a+b) = [tan(a) +tan(b)]\[1-tan(a)tan(b)]

-17/6 = [8 + tan(b)]/[1-8tan(b)]

-17[1-8tan(b)] = 6[8+tan(b)]

-17 +136 tan(b) = 48 + 6tan(b)

130tan(b) = 65

tan(b) =.5

Results 1 to 5 of 5

- May 6th 2009, 06:38 AM #1

- Joined
- Jul 2008
- From
- NYC
- Posts
- 1,489

- May 6th 2009, 07:05 AM #2

- May 6th 2009, 09:39 AM #3

- Joined
- Jul 2008
- From
- NYC
- Posts
- 1,489

- May 6th 2009, 09:47 AM #4

- May 6th 2009, 02:56 PM #5

- Joined
- Jul 2008
- From
- NYC
- Posts
- 1,489